Shaping health security strategy: the influence of CSIS on US policy formulation - Liu, Jiangwei; Sity Daud, (Penerbit UKM, 2024)
Think tanks have long been viewed as an important player in the policy-making of US government. However, in an era of global health threats, less attention has been given on how they engage in health security issues thus affecting policy-making of the government. This study first reviews the historical and evolving paradigms of health security, tracing its conceptual development from its roots in the mid-20th century to its contemporary relevance. Taking the Center for Strategic and International Studies (CSIS), a well-known and comprehensive think tank of the United States, as the research subject, this study then explores its role in the formulation of health security policies of the United States. The study reveals that CSIS significantly influences the health security policies of the United States by conducting strategic analyses, offering evidence-based recommendations, and serving as a critical platform for dialogue between health experts, policymakers, and government officials. By bridging research and practical policymaking, CSIS not only provides actionable insights but also facilitates inter-agency collaboration and global health security strategies.